Analisis Kemampuan Berpikir Kritis Peserta Didik dalam Menyelesaikan Soal Matematika Kelas X MIPA SMAN 13 Padang - Arlin, Delia; Wahyuni, Yusri; Herawati, Susi; Desfitri, Rita; Fauziah (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2023)
Critical thinking skills play a crucial role in education development, especially in the context of mathematics learning in schools. Unfortunately, research indicates that students' critical thinking abilities in class X MIPA 2 at SMAN 13 Padang are still low. During the learning process, students tend to focus solely on the final formulas provided by their teachers without attempting to understand the underlying steps, often resorting to copying them into their notes. Therefore, this research aims to describe and analyze students' critical thinking abilities in solving mathematics problems in class X MIPA at SMAN 13 Padang.The research employs a qualitative method with a descriptive research design. The research subjects involve all students in class X MIPA 2 at SMAN 13 Padang, selected through a purposive sampling technique. The research instruments consist of a critical thinking ability test followed by interviews with six students, each representing high, medium, and low-performing groups based on the critical thinking ability test results. The research findings indicate significant variations in the critical thinking abilities of students in class X MIPA 2 at SMAN 13 Padang. The high-performing group achieved 21.21%, the medium-performing group reached 63.63%, while the low-performing group only reached 15.15%.